Value conflict in study of social change in India - Roy, Girish Chandra (New Delhi, 1983)
Study of Indian sobriety and social change in Indie with a theoretical frame-work based Western ontology poses a value conflict for Indian Socioogist. At the same time, for the study of Indian society and social change in it a scientific frame of reference, a. Value- free" frame-work, is of, utmost on This requires a importance. scientific social examination of the intellectual locus and moral foundation of Indian thought. This constitutes the content and purpose of this book. In the analytical frame-work adopted in the book, Indian value system is analyzed from a global perspective, as one among "many," with a stress on conflict involved from Wes- tern impact. Different perspec- tives and approaches relating to the study of economic develop- ment are reviewed. change in India is analyzed from the point of view of an insider where intellectual relationships between value system of Indian and Western society are taken to be data science analysis. Indian value system is shown to objective role in change. The objective is to develop a broad theoretical frame-work which encompasses the sphere of relationships involving between values of two civilizations-Indian and Western.
Keywords: Sociology .